Host‐specific competitiveness to form nodules in Rhizobium leguminosarum symbiovar viciae. Issue 2 (28th January 2020) - Boivin, Stéphane; Ait Lahmidi, Nassima; Sherlock, David; Bonhomme, Maxime; Dijon, Doriane; Heulin‐Gotty, Karine; Le‐Queré, Antoine; Pervent, Marjorie; Tauzin, Marc; Carlsson, Georg; Jensen, Erik; Journet, Etienne‐Pascal; et al.
Summary: Fabeae legumes such as pea and faba bean form symbiotic nodules with a large diversity of soil Rhizobium leguminosarum symbiovar viciae ( Rlv ) bacteria. However, bacteria competitive to form root nodules (CFN) are generally not the most efficient to fix dinitrogen, resulting in a decrease in legume crop yields. Here, we investigate differential selection by host plants on the diversity of Rlv . A large collection of Rlv was collected by nodule trapping with pea and faba bean from soils at five European sites. Representative genomes were sequenced. In parallel, diversity and abundance of Rlv were estimated directly in these soils using metabarcoding. The CFN of isolates was measured with both legume hosts. Pea/faba bean CFN were associated to Rlv genomic regions. Variations of bacterial pea and/or faba bean CFN explained the differential abundance of Rlv genotypes in pea and faba bean nodules. No evidence was found for genetic association between CFN and variations in the core genome, but variations in specific regions of the nod locus, as well as in other plasmid loci, were associated with differences in CFN. These findings shed light on the genetic control of CFN in Rlv and emphasise the importance of host plants in controlling Rhizobium diversity.